2019
DOI: 10.1002/jclp.22884
|View full text |Cite
|
Sign up to set email alerts
|

The role of resources in the face of psychopathology

Abstract: Objectives The current study compared resource realization and psychological distress in patients with different psychiatric diagnoses and healthy individuals and examined the moderating effect of intrapersonal resources (personal strengths) and interpersonal resources (relationships) on the association between incongruence (unsatisfactory realization of personal goals) and psychological distress. Method In total, 218 participants (45.87% female, mean age = 39.83 years) completed standardized questionnaires at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Patients in the strengths‐oriented module profited significantly more ( d = 0.69, p = 0.03). Concurrently, strengths seem to be less accessible for patients: two recent studies showed that clinical samples before treatment report significantly lower levels of currently perceived strengths compared to healthy individuals (Goldbach et al, 2019; Victor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the strengths‐oriented module profited significantly more ( d = 0.69, p = 0.03). Concurrently, strengths seem to be less accessible for patients: two recent studies showed that clinical samples before treatment report significantly lower levels of currently perceived strengths compared to healthy individuals (Goldbach et al, 2019; Victor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The independence of WIRF subscales also provide practical implications: Although recent studies indicated that patients perceive fewer current strengths than healthy individuals, this does not mean that strengths to cope with their problems do not exist ( Goldbach et al, 2020 ; Victor et al, 2019 ). The results of this study highlight that it makes sense for therapists to actively address existing strengths to further foster mental health.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of psychopathology appear to be associated with negativity biases, which may be one reason why patients have less access to their own strengths that are present despite their distress ( Stanton & Watson, 2014 ; Trompetter et al, 2017 ). With respect to this, two studies showed that both psychiatric inpatients and psychotherapy outpatients report significantly lower levels of self-perceived strengths compared to healthy individuals with large effect sizes for this difference ( Goldbach et al, 2020 ; Victor et al, 2019 ). Most available instruments assess strengths over all situations a person experiences (trans-situational).…”
mentioning
confidence: 99%
“…optimism, social support; Taylor & Broffman, 2011 ). Previous findings indicated moderate to high correlations between different constructs and the possibility to assess a generic perception of inherent resources ( Goldbach et al, 2020 ; Taylor & Broffman, 2011 ; Victor et al, 2019 ). Psychological resilience was defined as the potential to successfully adapt to adversities and stressors ( Davydov et al, 2010 ).…”
Section: Pa and Psychological Processesmentioning
confidence: 98%